2012
DOI: 10.1007/s10396-012-0357-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on temperature rise of acoustic radiation force elastography

Abstract: In conclusion, the imaging area, including the path of the push wave, should be carefully checked and the time interval for consecutive use should be adjusted to prevent thermal risk on the surface of the bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The ARFI elastography was performed without discomfort to the pregnant bitches and there was no evidence of alterations in the factors being evaluated as result of the use of this technique, considering it a safe and a non-invasive approach. There were similar observations by Tabaru et al (2012) in a study on the biological effects of ultrasonography in fetal evaluation. These findings were verified by Sugitani et al (2013) in women when there was reporting that, microscopically, there were no structural, thermal, or mechanical changes in the tissues studied.…”
Section: Discussionsupporting
confidence: 79%
“…The ARFI elastography was performed without discomfort to the pregnant bitches and there was no evidence of alterations in the factors being evaluated as result of the use of this technique, considering it a safe and a non-invasive approach. There were similar observations by Tabaru et al (2012) in a study on the biological effects of ultrasonography in fetal evaluation. These findings were verified by Sugitani et al (2013) in women when there was reporting that, microscopically, there were no structural, thermal, or mechanical changes in the tissues studied.…”
Section: Discussionsupporting
confidence: 79%
“…The BMUS guidelines for the safe use of diagnostic ultrasound equipment (BMUS Safety Group 2010) suggests using the bone thermal index for obstetric scans after the 10 th week. Many other studies have shown that heating of bones is much higher than that of soft tissues (Tabaru et al 2012;Nitta et al 2001). Further studies should be performed on phantoms containing soft tissues and bone mimicking materials.…”
Section: Discussionmentioning
confidence: 95%
“…17 The radiation force based elastography (ARFI, SWE) though involves higher TI, it is still within limits set by American Institute of Ultrasound in Medicine and risk considerations are similar to the Doppler imaging mode. 17,[136][137][138] Funding None.…”
Section: Potential Riskmentioning
confidence: 99%